The Future of Wood - towards circular bioeconomy - Hetemäki, L.; Nasi, R.; Palahi, M.; Cerutti, P.O.; Mausch, K. (Center for Open Science, 2021)
In summary, there are great opportunities to better use wood as a non-fossil fuel-based raw materials and tackle climate change, as well as to achieve Sustainable Development Goals. However, there is an urgent need to invest in more research on how this could be best implemented in a sustainable way and in different regions, especially in the global South.